(untitled) (Research, Society and Development, 2023)
Objective: to analyze the available scientific evidence on the use of communication technologies used to facilitate interaction between family members and patients hospitalized in ICUs and ILP. Method: scope review, carried out according to the model proposed by the Joanna Briggs Institute, through the review of the databases: MEDLINE (PubMed), LILACS, EMBASE, CINAHL, SCOPUS, WEB OF SCIENCE and PSYCINFO. All types of methodological design, published in English, Spanish and Portuguese, involving health communication technologies applied to critical and non-critical patient care (for example: video calls, videoconferences, etc.) long stay. Results: 15 studies were included that verified video calling as the main strategy and the following benefits: improvement in communication and bonding between physicians, patients and their families, decrease in sedation, agitation, delirium, depression, time in coma and length of stay in the ICU and the negative effects of isolation and loneliness. Conclusion: despite the variable methodological quality of the studies, the use of communication technologies in environments where the patient needs to be isolated from his family has benefits, greater than their disadvantages or limitations for the clinical recovery of patients.